Hydraulic processes in roots and the rhizosphere pertinent to increasing yield of water-limited grain crops a critical review - Ahmed, Mutez Ali (Journal of experimental botany, 2018)
HIGHLIGHT: A review of the role of roots in extracting water from the soil with regard to amount and timing leading to maximal grain yield, and of the various mechanisms underlying this